Effects of Ozone Treatments on the Physicochemical Changes of Myofibrillar Proteins from Silver Carp (Hypophthalmichthys molitrix) during Frozen Storage - Rongrong Zhang; Shanbai Xiong; Juan You; Yang Hu; Ru Liu; Tao Yin (Journal of Food Quality)
Physicochemical changes of myofibrillar proteins from silver carp surimi during frozen storage as affected by two manners of ozone treatments were investigated. For preparation of surimi treated with ozone, ozone water (8 mg/L) was used in either the first (To1) or the second (To2) cycle of rinsing. As compared with control samples (Tc) (rinsing two cycles with water), myofibrillar proteins from To1 surimi showed slightly lower free sulfhydryl contents and higher surface hydrophobicity throughout frozen storage and lower Ca2+-ATPase activities after 30 d. To2 did not significantly (P>0.05) affect these physicochemical properties, indicating that myofibrillar proteins structure was well maintained. Consequently, To1 significantly (P>0.05) decreased breaking force of surimi gels while To2 did not significantly (P>0.05) affect gel breaking force. In addition, the whiteness of surimi gels was increased more obviously by To2 than by To1. The results indicate that To2 could be used as a mild oxidation treatment for improving white color of silver carp surimi without negatively affecting gel texture.